Minimally Invasive Approach for Improving Anterior Dental Aesthetics: Case Report with 1-Year Follow-Up - H. Sevilay Bahadır; Gökhan Karadağ; Yusuf Bayraktar (Case Reports in Dentistry)
Dental aesthetics have become highly important in recent years. Treating aesthetic demands with noninvasive or minimally invasive techniques can preserve the natural tissues. A 20-year-old female patient presented to the clinic with aesthetic concerns. After the clinical and radiographic examinations, hypomineralization was identified in the maxillary anterior teeth except the maxillary right canine. An external discoloration was also identified in the maxillary left canine tooth. Moreover, the right canine tooth was identified as a Turner’s tooth according to the patient’s anamnesis. The resin infiltration technique was applied to the maxillary anterior teeth except the maxillary right canine. The bleaching treatment was applied to the maxillary left canine tooth. Then, a laminate veneer restoration was applied to the upper right canine tooth with Turner’s hypoplasia. Following the treatment, a satisfactory aesthetic restoration was achieved. After 1-year examination, no clinical failures were observed.